Calendars, Compliments, and Computations: A Comparative Survey of the Canon in the Persian Zīj-i Šāh Jahānī and in its Sanskrit translation, the Siddhāntasindhu - Arzoumanov, Jean; Misra, Anuj (History of Science in South Asia)

(untitled) (University of Alberta Library, 2023)
Various studies in recent times have shown how sociohistorical proclivities played an important role in the acceptance or rejection of cross-cultural ideas in Mughal scientific discourses. The cultural patronage of the Mughal courts financed the production and propagation of certain scientific texts deemed intellectually and politically expedient. Among such texts were two seventeenth-century astronomical table-texts, Mullā Farīd's Persian Zīj-i Šāh Jahānī and its Sanskrit translation in Nityānanda's Siddhāntasindhu, both produced at the court of the Mughal Emperor Šāh Jahān.In this paper, we present, for the very first time, a comparative survey of the canon (text) of these two works to reveal the intimacy between the translated Sanskrit and its Persian original. The paper includes brief biographies of both astronomers, a summary of the salient features of the canons, a description of the manuscripts utilised and our transcription and transliteration schemes, along with a detailed comparison of the individual chapters in these canons. We also provide separate appendices with discussions on select aspects from these chapters. We note that this paper forms the first part in a two-part study, with a second forthcoming paper surveying the tables in these two texts (accompanied with mathematical annotations).